Pengaruh Intellectual Capital Disclosure Terhadap Cost Of Equity Dan Cost Of Debt - Ira Khoirunnisa; Ari Dewi Cahyati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
Objective of this study is determine the effect the intellectual capital disclosure on cost of equity and cost of debt studies on companies in property and real estate in the Indonesia Stock Exchange from 2013 to 2015. The method used is quantitative approach. Data of this research is secondary data, using the financial statements of companies listed in the Stock Exchange gained through www.idx.co.id. 2013-2015 Samples were selected using purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the human capital disclosure, structural capital disclosure have no significant positive effect and customer capital disclosure have no significant negative effect to cost of equity. Then human capital disclosure have no significant positive effect and structural capital disclosure, customer capital disclosure have no significant negative effect to cost of debt.